Power output of field-based downhill mountain biking - Hurst, H. T.; Atkins, S. (Journal of Sports Sciences, 2006)
The purpose of this study was to assess the power output of field-based downhill mountain biking. Seventeen trained male downhill cyclists (age 27.1 ± 5.1 years) competing nationally performed two timed runs of a measured downhill course. An SRM powermeter was used to simultaneously record power, cadence, and speed. Values were sampled at 1-s intervals. Heart rates were recorded at 5-s intervals using a Polar S710 heart rate monitor. Peak and mean power output were 834 ± 129 W and 75 ± 26 W respectively. Mean power accounted for only 9% of peak values. Paradoxically, mean heart rate was 168 ± 9 beats · min-1 (89% of age-predicted maximum heart rate). Mean cadence (27 ± 5 rev · min-1) was significantly related to speed (r = 0.51; P < 0.01). Analysis revealed an average of 38 pedal actions per run, with average pedalling periods of 5 s. Power and cadence were not significantly related to run time or any other variable. Our results support the intermittent nature of downhill mountain biking. The poor relationships between power and run time and between cadence and run time suggest they are not essential pre-requisites to downhill mountain biking performance and indicate the importance of riding dynamics to overall performance.